2020
DOI: 10.1097/aln.0000000000003207
|View full text |Cite
|
Sign up to set email alerts
|

Neurally Adjusted Ventilatory AssistversusPressure Support Ventilation in Difficult Weaning

Abstract: Background Difficult weaning frequently develops in ventilated patients and is associated with poor outcome. In neurally adjusted ventilatory assist, the ventilator is controlled by diaphragm electrical activity, which has been shown to improve patient–ventilator interaction. The objective of this study was to compare neurally adjusted ventilatory assist and pressure support ventilation in patients difficult to wean from mechanical ventilation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 24 publications
0
48
0
2
Order By: Relevance
“…Since all that is set during NAVA is the proportion of effort provided by the ventilator to supplement the patient's ventilatory drive, for a given NAVA level, the airway pressure varies breath-by-breath in proportion to Edi. Three randomized controlled trials on NAVA have been previously published [9,11,12]. Demoule et al [9] randomized 128 patients ready for partial ventilatory support to NAVA or pressure support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all that is set during NAVA is the proportion of effort provided by the ventilator to supplement the patient's ventilatory drive, for a given NAVA level, the airway pressure varies breath-by-breath in proportion to Edi. Three randomized controlled trials on NAVA have been previously published [9,11,12]. Demoule et al [9] randomized 128 patients ready for partial ventilatory support to NAVA or pressure support.…”
Section: Discussionmentioning
confidence: 99%
“…Although they also reported fewer hospital deaths in the NAVA group, no significant differences were observed in ICU, 28-day, or 90-day mortality. Most recently, Liu et al [12] randomized the use of NAVA and pressure support in 99 difficult-to-wean patients. They observed that NAVA reduced the time of weaning and increased VFDs, with no effects on ICU, 28-day, or hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Also, diaphragm inactivity due to over-assistance is unlikely in NAVA, as low diaphragm activity will immediately reduce inspiratory assist. Future studies should confirm the role of NAVA in lung and diaphragm-protective ventilation, but recent randomized trials suggest clinical benefit of NAVA (reduced time on the ventilator) compared to pressure support mode [ 40 , 41 ].…”
Section: Clinical Strategies To Facilitate Lung and Diaphragm-protectmentioning
confidence: 99%
“…A recent study confirmed acceptable adherence to the assigned mode beyond 48 h when comparing NAVA with PSV [21]. Furthermore, Liu et al recently showed shorter weaning duration with NAVA compared to PSV in selected difficult-to-wean patients [20].…”
Section: Clinical Comparisons Of Proportional Modes and Psvmentioning
confidence: 82%
“…Moreover, safe targets for respiratory effort may vary among patients, depending on the severity of lung injury and diaphragm function [15][16][17]. The uncertainty regarding titration of inspiratory support with NAVA and PAV+ might be one of the reasons why there is still limited data showing improved clinical outcomes when using proportional modes as compared to conventional modes [18,19], but clinical benefits of NAVA compared to PSV were recently demonstrated in difficult-to-wean patients [20,21]. At the same time, despite having very complex physiological consequences, PSV maintains an appearance of simplicity and is the most frequently used partially supported mode of ventilation [22].…”
Section: Introductionmentioning
confidence: 99%